A green, facile, and rapid method for microextraction and Raman detection of titanium dioxide nanoparticles from milk powder. Issue 35 (18th April 2017) - Zhao, B.; Cao, X.; De La Torre-Roche, R.; Tan, C.; Yang, T.; White, J. C.; Xiao, H.; Xing, B.; He, L.
Abstract : A green, facile, and rapid method for microextraction and Raman detection of titanium dioxide nanoparticles from milk powder is reported. Abstract : Titanium dioxide (TiO2 ) has been widely used as a common ingredient in numerous food products. Recently, the analysis of TiO2 nanoparticles (NPs) has attracted increasing attention due to potential risks to human health and the environment. Herein, we present a green, facile, and rapid method using flavonoid-assisted microextraction and Raman spectroscopy for TiO2 NPs (anatase, 21 nm) detection in real food samples. Flavonoids can bind onto TiO2 NPs, enabling the microextraction of the particles by ethyl acetate and sodium chloride. The extracted TiO2 NPs concentrate at the interlayer and are easily removed for analysis by Raman spectroscopy. By taking advantage of surface-enhanced Raman spectroscopy (SERS), we evaluated and selected the best binding flavonoid, myricetin (MYC) bound onto TiO2 NPs, and were able to achieve detection at concentrations as low as 0.2 mg L −1 TiO2 NPs in water. The method was successfully challenged in the presence of various interferences from common food components and different pH conditions. The recoveries determined using inductively coupled plasma mass spectrometry (ICP-MS) ranged from 66.6% to 88.3%. More important, the method showed good capability for the extraction and quantification of TiO2 NPs from infant milk powder dilutions. As flavonoids, ethyl acetate, and sodium chloride have low toxicity and are relatively abundant in the environment, this may be considered a green approach for TiO2 NP extraction and detection. The developed method in this study holds great potential for rapid (<1 h) detection of TiO2 NPs from food products.